Pluralism And Freedom Of Religion In Indonesia In Context Of The Religious Blasphemy Prevention Act - Johannes Johny Koynja (Unram Law Review, 2018)
The point of the problem spectrum that becomes the legal issue in this article is in the establishment of the Act Number 1/PNPS/1965 on Prevention of Abuse and/or Blasphemy to the Religion as requested its examination to the Constitutional Court. The Constitutional Court of the Republic of Indonesia in its decision assess that the Applicant, in fact, wishes only to look for interpretation and form "freedom of religion and confidence" in Indonesia. For that, the legal analysis was done to the problem of pluralism of religion in Indonesia it's bearing on the implementation of the Religious Blasphemy Prevention Act, ideally, include three analysis, that is governance science (bestuurkundige), human rights, and freedom of religion values analysis of requested its examination to the Constitutional Court. Discussion concerning relations among religion and state become to draw to be studied by its bearing about how the ought relationship of religion and state in Indonesia society embracing pluralism. The freedom of religion and confidence, in fact, do not represent absolute matter the religious believers to free and ease, but Also have to at one's feet of demarcation the religious believers there are in Article 28J of the sentence (2) The 1945 Constitution of the Republic of Indonesia as the supreme law of the which represent Staatsfundamentalnorm roommates giving guidance of freedom of religion and confidence in Indonesia. In the context needed or it's not the Religious Blasphemy Prevention Act, all-important only how State or Government able give the guarantee that law and regulation the which published can become base management of conflict between society the which is plural wisely and can become socio-cultural supporter national tighten tying, arrange the democratic system and governance, so that various distortion potency flange at the happenings of interfaith conflict, internal conflict and external Also can lessen, not simply forming and equipping peripherals of law and regulation.